Direct observation of band bending in the topological insulator Bi 2Se3 - Violbarbosa, C. E.; Shekhar, Chandra; Yan, Binghai; Ouardi, Siham; Ikenaga, Eiji; Fecher, G. H.; Felser, Claudia (Physical Review B - Condensed Matter and Materials Physics, 2013)
The surface band bending tunes considerably the surface band structures and transport properties in topological insulators. We present a direct measurement of the band bending on the Bi2Se3 by using the bulk sensitive angular-resolved hard x-ray photospectroscopy (HAXPES). We tracked the depth dependence of the energy shift of Bi and Se core states. We estimate that the band bending extends up to about 20 nm into the bulk with an amplitude of 0.23-0.26 eV, consistent with profiles previously deduced from the binding energies of surface states in this material. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20